(untitled) (Research, Society and Development, 2021)
The three pedagogical moments are a methodology that seeks to increase interest and encourage student learning, using themes present in their daily lives. Thus, the present work aims to develop and apply a didactic sequence based on the three pedagogical moments. With this, the sequence was developed for first-year classes of young people and adults using the theme "Chemistry and Food", in the first pedagogical moment, the initial problematization stage was taken to the students with problematizing questions to survey prior knowledge. Right after, in the second pedagogical moment of contribution of the framework, application, support texts and questions, the content of inorganic functions was raised, always linking to the generating theme. Finally, in the last pedagogical moment, a game and a question were used to extrapolate the content. The didactic sequence proved to be an important teaching tool, because following the analysis of the results, the students had an effective learning in the end. This teaching tool also promotes debate within the classroom, making students become more citizens. critics and active in the world in which they live.